2014
DOI: 10.1093/ehjci/jeu287
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of dynamic pulmonary vascular resistance in two populations at risk of pulmonary arterial hypertension

Abstract: AimsPatients at risk of pulmonary arterial hypertension (PAH) may present with abnormal dynamic pulmonary vascular resistance (PVR) during exercise. However, its clinical significance remains unclear. The present study aimed at analysing the meaning of dynamic PVR in two populations at risk of PAH: secundum atrial septal defect (ASD) and systemic sclerosis (SSc). Methods and resultsAdult patients with corrected ASD were consecutively selected from the database of Pediatric and Congenital Heart Disease of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Patients at risk of PAH or pulmonary hypertension Certain conditions are associated with a significantly increased risk of PAH, in particular SSc, which is often used as a model to investigate the development of PAH and recognise early markers of PAH development [38,39]. Based on recent studies, exercise pulmonary hypertension may represent early pulmonary vascular involvement in SSc and may be predictive for development of PAH [129,[131][132][133][134][135]. In SSc, an abnormal PAP increase during exercise may result from pulmonary vasculopathy [37,41,43], but also from parenchymal lung disease and left heart disease [43,130,133,134,[136][137][138].…”
Section: Pulmonary Haemodynamics During Exercise In Special Patient Gmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients at risk of PAH or pulmonary hypertension Certain conditions are associated with a significantly increased risk of PAH, in particular SSc, which is often used as a model to investigate the development of PAH and recognise early markers of PAH development [38,39]. Based on recent studies, exercise pulmonary hypertension may represent early pulmonary vascular involvement in SSc and may be predictive for development of PAH [129,[131][132][133][134][135]. In SSc, an abnormal PAP increase during exercise may result from pulmonary vasculopathy [37,41,43], but also from parenchymal lung disease and left heart disease [43,130,133,134,[136][137][138].…”
Section: Pulmonary Haemodynamics During Exercise In Special Patient Gmentioning
confidence: 99%
“…In addition, abnormal haemodynamic responses, measured either by exercise Doppler echocardiography or by RHC during exercise have been reported in family members of idiopathic or heritable PAH patients [29,121,139,140], in patients susceptible to high-altitude pulmonary oedema [28], in chronic thromboembolic disease [53,89,141], post-repair congenital heart disease (closed atrial septal defect) [134], lung disease [93,142,143], chronic heart failure [78] and valvular heart disease patients [144,145]. It is not clear whether any of these conditions is associated with PAH.…”
Section: Pulmonary Haemodynamics During Exercise In Special Patient Gmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors observed that the slope of change in the relationship between PASP and cardiac index (CI) was significantly greater than in controls. In this regard, echo assessment of increased pulmonary vascular resistance and left ventricular filling pressure during exercise could represent a more specific diagnostic (precapillary vs postcapillary PH) and prognostic marker of patients with overt PH and/or at higher risk of PH …”
Section: Stress Echocardiographymentioning
confidence: 96%
“…These authors observed that the slope of change in the relationship between PASP and cardiac index (CI) was significantly greater than in controls. In this regard, echo assessment of increased pulmonary vascular resistance and left ventricular filling pressure during exercise could represent a more specific diagnostic (precapillary vs postcapillary PH) and prognostic marker of patients with overt PH and/or at higher risk of PH 50,51. Interestingly, in a series of 124 patients with PAH or inoperable chronic thromboembolic PH and impaired RV pump function, Grünig et al52 showed that patients with low RV contractile reserve who were not able to increase sPAP during exercise had a significantly worse prognosis and needed intensified treatment.…”
mentioning
confidence: 99%